POLA PENDISTRIBUSIAN DAN EFEKTIFITAS FUNDRISING ZAKAT PADA PROGRAM KESEHATAN DI MASA PADEMI COVID-19 - Dede Aji; Muhammad Abduh (Al-Maslahah : Jurnal Ilmu Syariah, 2022)
The purpose of this study is the measurement and mapping of the zakat distribution system and the pattern of zakat distribution in health services in Dompet Peduli Umat Daarut Tauhid (DPU-DT). The method used is qualitative with interview techniques to mustahik and muzaki as well as administrators with purpose sampling and snowball sampling. From the results of the study it was found that so far the pattern of zakat distribution has been going well with direct and indirect funding distribution patterns. The obstacle faced in fundrising is the prohibition on gathering and crowding because it is still in the covid-19 pandemic. In addition, the obstacle faced is the data accuracy factor that is not synchronized between the BPS database and the reality in the community Keywords: Fundrising DPU-DT, Zakat and Covid-19